Income inequality, good governance and crime in some selected European countries - Buba, Saad (2019)
The goal of this thesis is to study the relationship between income inequality and crime in Europe over the period of 1993 – 2014. Income inequality has been identified as one of the major problems facing developed, emerging, and less developed countries. Europe is a continent with more developed countries. Yet, the United Kingdom recorded a relatively high Gini coefficient. Turkey has the highest income disparity coefficient and the same goes to Greece, Portugal, France, Italy, Germany, and Spain. However, little empirical evidence is established on the effects of income inequality on the property crime rate. Theoretical considerations suggest that income inequality may have imperative longrun implications on crime rates. However, empirical studies on this relationship have produced mixed findings. Most existing studies disregard the impact of the rule of law (governance) in estimating the determinants and long-run growth effects of income inequality. The present multicollinearity in analysing the interaction effects of income inequality has also led to ambiguous results. In view of these problems, this study is set to examine (i) the effects of income inequality and rule of law on crime in Europe, (ii) the impacts of trade liberalisation on income inequality in Europe, and (iii) the impacts of real gross domestic product (GDP) per capita and income inequality on rule of law in Europe using orthogonalised interaction effects, which provide solution to the multicollinearity problem and Pooled Mean Group (PMG) estimator for all objectives on panel data of 31 European countries, namely 17 countries from the Nordic and Western Europe and 14 countries from the Southern and Eastern Europe, over the period of 1993-2014. The inclusion of rule of law and its interaction with income inequality is the major contribution of this study. Property crime is used as a measure of crime. The findings revealed significant evidence, which validates the view of theories and earlier findings that equality of income distribution, good governance, a higher level of educational attainment, and employment rate have a significant relationship with crime rates. The interactive term of income inequality and rule of law revealed a negative effect on property crime. The results revealed significant evidence on the relationship between trade liberalisation in the form of tariff reduction on manufactured goods and financial liberalisation with income inequality in Europe. The findings also showed significant evidence that, in the case of Europe, real GDP per capita growth negatively impacts rule of law. A higher level of education positively influences rule of law, which validate the assertion that educational attainment uplifts the quality of rule of law. Trade openness, on the other hand, negatively determines rule of law in Europe. Other factors like tariff reduction on manufactured goods and the level of income inequality positively and negatively impact rule of law, respectively. The study suggests that pursuing policies related to redistribution of income towards the reduction of social and economic inequality as well as improving the quality of rule of law in order to reduce crime are likely to be successful.